Orthosis Effects on the Gait of a Child with Infantile Tibia Vara - Serap Alsancak; Senem Guner (Case Reports in Pediatrics)
Infantile tibia vara (ITV) is an acquired form of tibial deformity associated with tibial varus and internal torsion. As there is currently insufficient data available on the effects of orthotics on gait parameters, this study aimed to document the influence of orthosis on walking. A male infant with bilateral tibia vara used orthoses for five months. Gait evaluations were performed pre- and posttreatment for both legs. The kinematic parameters were collected by using a motion analysis system. The orthotic design principle was used to correct the femur and tibia. Posttreatment gait parameters were improved compared to pretreatment parameters. After 5 months, there was remarkable change in the stance-phase degrees of frontal plane hip joint abduction and knee joint varus. We found that orthoses were an effective treatment for the infantile tibia vara gait characteristics in this patient. Full-time use of single, upright knee-ankle-foot orthosis with a drop lock knee joint and application of corrective forces at five points along the full length of the limb were effective.